Studi Hadis tentang Kebohongan yang Diperbolehkan (Kajian Tematik Hadis) - Ulumia Mukhlis (Jawahir Al-Ahadis, 2025)
Lies are words or actions that do not match existing reality. There are verses from the Qur'an and the words of the Prophet Rasulullah which clearly prevent lying, but on the other hand there are hadiths, as well as several histories regarding the ability to make excuses. The purpose of this research is to identify the quality and description of the permitted words of false prophets. After that, it is hoped that it will bring benefits to increase knowledge and understanding so that it can be applied in everyday life. This research is categorized as qualitative research in the form of a bibliography (Library Research), using the Maudhu'i method, which is useful for studying the quality of the prophet's words and explanations of the prophet's words. In the initial stage, the prophet's words were traced in the book Mu' jam al-Mufahras li Alfadz al-Hadith. After that, refer to the source book of the Prophet's sayings, then try to interpret the Prophet's sayings to determine the quality of the hadiths which have been examined using the Maudhu'i method. After that, try to interpret it by analyzing the description of the prophet's words from the related book of Syarah on the Prophet's Sayings to get the first explanation of the 3 permissible views of lying. The hadiths that have been examined are generally the words of the prophet with authentic quality. There are also narrators who have problems with the prophet's words until the prophet's words are hasan, but there are uniform prophet's words which are narrated by Sahih Bukhari and Sahih Mukmin until the prophet's words rise to the level of Sahih Lighairihi. After that, there is an explanation regarding the prohibition against lying, this prohibition is not absolute, because there are 3 situations where it is permissible to make excuses, namely arguing in a limited war, not only a security agreement, arguing to reconcile, such as a believer who is hiding because he is being chased by an unjust person who will kill him. so in this case you have to make excuses to prevent the person, and the husband's lying to his wife is limited to issues that do not invalidate rights. A person's ability to make excuses is related to the circumstances and situations in which it is permissible, if something that is informed is good and can be informed without lies, so in this situation, arguing is taboo. However, if it cannot be conveyed except by making excuses, then in this case lying is required.